Suppressing effect of saikosaponin A, an active ingredient of Bupleurum falcatum, on chocolate self-administration and reinstatement of chocolate seeking in rats. (18th January 2017) - Lorrai, Irene; Maccioni, Paola; Carai, Mauro A.M.; Capra, Alessandro; Castelli, M. Paola; Riva, Antonella; Morazzoni, Paolo; Gessa, Gian Luigi; Colombo, Giancarlo
Highlights: Saikosaponin A is a major ingredient of the medicinal herb, Bupleurum falcatum . Saikosaponin A reduced self-administration of a chocolate-flavored beverage in rats. Saikosaponin A also reduced reinstatement of seeking for a chocolate-flavored beverage. These results extend the anti -addictive effect of saikosaponin A to a natural stimulus. Abstract: Recent lines of experimental evidence have indicated that saikosaponin A (SSA) – a bioactive ingredient of the medicinal plant, Bupleurum falcatum L. – suppressed alcohol, morphine, and cocaine self-administration in rats. The present paper was designed to assess whether the protective properties of SSA on addiction-related behaviors generalize to a hyperpalatable food such as a chocolate-flavored beverage (CFB). To this end, rats were initially trained to lever-respond for CFB [5% (w/v) Nesquik ® powder in water] under fixed ratio (FR) 10 (FR10) schedule of reinforcement. Once lever-responding reached stable levels, rats were treated acutely with two different dose ranges of SSA (0, 0.25, 0.5, and 1 mg/kg; 0, 1, 2.5, and 5 mg/kg; i.p.) and exposed to the FR10 and progressive ratio (PR) schedules of reinforcement in four independent experiments. The effect of acutely administered SSA (0, 0.25, 0.5, and 1 mg/kg; i.p.) on cue-induced reinstatement of seeking behavior for CFB was also assessed. Under the FR and PR schedules of reinforcement, treatment with SSA diminished lever-responding for CFB, amount of self-administered CFB, and breakpoint for CFB. All variables were virtually completely suppressed after treatment with 5 mg/kg SSA. Treatment with SSA also suppressed reinstatement of CFB-seeking behavior. No dose of SSA altered rat motor-performance, evaluated exposing all rats to an inverted screen test immediately after the self-administration session. These results demonstrate that acute treatment with SSA potently suppressed several addictive-like behaviors motivated by highly hedonic nourishment. These data extend to a highly rewarding natural stimulus the anti-addictive properties of SSA recently disclosed in rats self-administering alcohol, morphine, and cocaine.